Perbandingan Efektivitas Madu Dengan Ekstrak Buah Bit (Beta Vulgaris) Terhadap Peningkatan Kadar Hemoglobin (Hb) Pada Remaja Putri - Ridni Husnah; Fitriani Fitriani; Dita Cahya Olivia (Jurnal Ners, 2025)
Adolescence is a form of transition from childhood to adulthood which is characterized by biological, cognitive, and emotional changes. Nutritional status of adolescents nationally, the prevalence of BMI/U in adolescents aged 13-15 years who are very thin and thin is 8.7%, normal 79.3%, obese and obese 11.9%. In adolescents aged 16-18 years who experience very thin and thin nutritional status, which is 8.1%, normal 7.8%, obese and obese 13.5%. Beetroot fruit has several nutrients contained, including, vitamins A, B, C. Beets are also a source of minerals such as phosphorus, calcium and iron. The purpose of this study is to prevent anemia in adolescent girls by giving Honey and Beetroot Extract. Methods This study uses a quasi-experiment using a Pre and Post-Test Research Design With Countrol Group. This study looked at the Effectiveness of Honey with Beetroot Fruit Extract (Beta Vulgaris) on Increasing Hemoglobin (Hb) Levels in Adolescent Girls before and after the intervention. Based on the results of Wilcoxon's ppst hoc in intervention group 1 and intervention 2 before and after being given beet extract and honey combination beet extract, P=0.001 was obtained greater than the value of p<0.005. This shows that the difference in hemoglobin levels in groups 1 and 2 has increased. This data was also seen after the Friedman test in intervention group 1 there was an increase in hemoglobin levels between before and after treatment with a difference of 37.62 and statistically significant with a value of p = 0.03 where p<0.05. So the results were obtained that there was a difference in hemoglobin levels before and after the administration of beet fruit extract and honey in the intervention group which increased significantly